Factors influencing adherence to antiretroviral therapy among HIV/AIDS patients at the Kendari City Regional General Hospital - Chintya Devi Oktovianus; Ramadhan Tosepu (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2024)
Background: AIDS (Acquired Immunodeficiency Syndrome) is a severe viral infection caused by HIV (Human Immunodeficiency Virus). Patients with HIV/AIDS require antiretroviral therapy to reduce viral load, prevent the spread of the virus, and maintain their quality of life. Adherence to antiretroviral treatment is crucial for achieving virological and therapeutic success and for preventing drug resistance. Objectives: This study aimed to analyze the factors influencing adherence to antiretroviral medication among HIV/AIDS patients at the Kendari City Regional General Hospital. Methods: This quantitative study included 73 respondents. Data were collected using a questionnaire and analyzed through multiple linear regression statistical tests. Results: The study found that both awareness of HIV/AIDS and family support significantly affected adherence to antiretroviral therapy, with a significance value of p = 0.000 (p < 0.05). Conversely, the side effects of antiretrovirals did not significantly impact adherence, with a significance value of p = 0.095 (p > 0.05). Conclusion: Awareness of HIV/AIDS patients is the most significant factor influencing adherence to antiretroviral treatment among HIV/AIDS patients at Kendari City Hospital. Keywords: HIV/AIDS awareness; family support; antiretroviral side effects; patient adherence